2022
DOI: 10.1186/s13046-022-02366-6
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop between gastric cancer cells and tumor-associated macrophage induces malignancy progression

Abstract: Background Hypoxia and inflammation tumor microenvironment (TME) play a crucial role in tumor development and progression. Although increased understanding of TME contributed to gastric cancer (GC) progression and prognosis, the direct interaction between macrophage and GC cells was not fully understood. Methods Hypoxia and normoxia macrophage microarrays of GEO database was analyzed. The peripheral blood mononuclear cell acquired from the healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
(58 reference statements)
0
25
0
Order By: Relevance
“…Macrophages are the most abundant immune cells in the tumor microenvironment [ 29 ]. The majority of macrophages in peritumoral AT are M2 macrophages, which exhibit high levels of CD163 expression [ 8 , 29 ]. M2 macrophages are known to promote progression and metastasis of gastric cancer cells [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are the most abundant immune cells in the tumor microenvironment [ 29 ]. The majority of macrophages in peritumoral AT are M2 macrophages, which exhibit high levels of CD163 expression [ 8 , 29 ]. M2 macrophages are known to promote progression and metastasis of gastric cancer cells [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD8 T cells and macrophages are the major immune cells in the tumor microenvironment of gastric cancer [ 35 ]. Macrophages in the tumor microenvironment predominantly exhibit an M2 phenotype with high CD163 expression [ 36 , 37 ]. M2 macrophages play a crucial role in promoting gastric cancer progression and metastasis and suppressing immune reactions in the tumor microenvironment, revealing a poor prognosis in tumors with increased M2 macrophage infiltration [ 10 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages in the tumor microenvironment predominantly exhibit an M2 phenotype with high CD163 expression [ 36 , 37 ]. M2 macrophages play a crucial role in promoting gastric cancer progression and metastasis and suppressing immune reactions in the tumor microenvironment, revealing a poor prognosis in tumors with increased M2 macrophage infiltration [ 10 , 37 ]. CD8 T lymphocytes are considered to perform important functions in anti-tumor reactions, and several studies have shown an improved prognosis in gastric cancers with a high density of CD8 T lymphocytes [ 10 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 (also known as CXCL8) is mainly produced by macrophages and plays a controversial role in regulating cancer progression [ 144 ]. Hypoxia increases IL-8 secretion significantly in macrophages but only slightly in gastric cancer (GC) cells [ 94 ]. Macrophage-derived CXCL8 induced by hypoxia can activate the JAK/STAT1 signaling pathway through binding to CXCR1/2 expressed on GC cells, leading to GC invasion and proliferation.…”
Section: Hypoxia-driven Crosstalk Between Tumor Cells and Tamsmentioning
confidence: 99%
“…The activation of STAT1 directly upregulates the expression of IL-10, stimulating M2 polarization of macrophages through the NF-κB signaling pathway. CXCL8 production is further encouraged by NF-κB activation [ 94 ].…”
Section: Hypoxia-driven Crosstalk Between Tumor Cells and Tamsmentioning
confidence: 99%